2009
DOI: 10.1021/nl9016623
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Organic Dispersions of Unfunctionalized Graphene

Abstract: We report a simple, high-yield, method of producing homogeneous dispersions of unfunctionalized and nonoxidized graphene nanosheets in ortho-dichlorobenzene (ODCB). Sonication/centrifugation of various graphite materials results in stable homogeneous dispersions. ODCB dispersions of graphene avert the need for harsh oxidation chemistry and allow for chemical functionalization of graphene materials by a range of methods. Additionally, films produced from ODCB-graphene have high conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
304
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(329 citation statements)
references
References 23 publications
16
304
1
2
Order By: Relevance
“…2a) showed that they contain graphene flakes with lateral size in range of ∼100-500 nm. The size of flakes correlates well with the values reported elsewhere using a sonication-assisted liquid exfoliation [14,20,23,44]. The thickness of the flakes was assessed with high resolution TEM (HRTEM) of flakes edges.…”
Section: Exfoliation Of Graphite To Graphenesupporting
confidence: 76%
See 1 more Smart Citation
“…2a) showed that they contain graphene flakes with lateral size in range of ∼100-500 nm. The size of flakes correlates well with the values reported elsewhere using a sonication-assisted liquid exfoliation [14,20,23,44]. The thickness of the flakes was assessed with high resolution TEM (HRTEM) of flakes edges.…”
Section: Exfoliation Of Graphite To Graphenesupporting
confidence: 76%
“…Irreversible exfoliation of graphite occurs when the surface energy of the solvent is close to the surface energy of graphite which overcomes Van der Waals forces between graphene sheets [14,20]. Among the best tested solvents are 1-methyl-2-pyrrolidinone (NMP) [20][21][22] and halogenated aromatic solvents [23,24]. Even though NMP is widely used in the preparation of electrodes for Li-ion batteries which makes it a natural choice, its toxicity and environmental hazard prompted research toward its replacement with environmentally friendly solvents [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Hence graphene holds potential for transparent conductive films (TCFs) application [50]. Graphene, the fascinating component of TCFs, can be fabricated by several methods: (1) GO-reduced graphene [51][52][53][54][55][56][57]; (2) graphene prepared by sonication of graphite in organic solvents, such as N-methyl-2-pyrrolidone and orthodichlorobenzene [58,59]; and (3) graphene grown on metal substrate by CVD [60][61][62][63]. The large scale productivity and low cost of GO-reduced graphene make it a superior candidate for the fabrication of TCFs.…”
Section: Transparent Conductive Filmsmentioning
confidence: 99%
“…While this method opened an avenue for many fundamental studies, it is likely impossible to scale for the production of larger quantities. The exfoliation of graphene in the liquid phase, by continuously sonicating graphite in a high surfacetension organic solvent [6,7], is another route to obtain mono-layered or few-layered sheets of graphene that are suspended in a dark mixture. However, the suspended graphene sheets tend to aggregate due to the lack of stabilizing groups such as surfactants or polymers to reduce interlayer attractions [8].…”
Section: Introductionmentioning
confidence: 99%